Making traditional modern : a phenomenological study of traditional confinement practices among urban Malay mothers - Syed Hussien, Sh Fatimah Alzahrah (2018)
Malay mothers’ postpartum experiences often include a period of confinement, similar to other Asian parallel practices of “doing the month”. This confinement period comprised of a set of beliefs, rules, and practices based on traditional eastern medicinal knowledge. Cultural practices of postpartum confinement, or berpantang, among urban mothers in Malaysia is evolving to compete with modern western medicine and technological advancement in the contemporary setting. The data for this presentation is based on twelve open-ended interviews of couples and two focus group discussions with mothers on their experience of berpantang. Even though it is still widely performed, the elements within berpantang are handpicked by these mothers and some of these elements have been repackaged to appeal to contemporary culture. According to these mothers, the traditional practices are thought to be inadequate when compared to the authority of western medicine. In events where medical practitioners give opposing advice, all mothers chose to adhere to, and accept modern medicine’s explanations and justifications over the traditional practice. The former cultural figure head, the bidan (midwife), is no longer a part of the birthing process within these urban settings. Urban mothers in the study rely on or refer to their maternal mothers for knowledge and guidance on berpantang. Urban mothers who practise berpantang describe the main reason for their practise was to maintain familial peace. I propose that the practise of berpantang is slowly losing its authority due to the lack of continuity in the chain of traditional knowledge and the hegemonic nature of modern medicine. Many of its features have also been packaged to fit the capitalistic nature of today’s world.